Should Positive Prescription on Land be Swept Away from the Sri Lankan Legal System as a Result of Introducing a Torrance System? - Chandrasiri, A. (My University, 2012)
Positive prescription1 is not an unfamiliar concept to Sri Lankan land law. The history of this concept dates back to Roman days when it had originated as a mode of acquiring land ownership under Roman Land law. Positive prescription became part of Sri Lankan land law when Roman-Dutch law was received by the Sri Lankan legal system. However, Roman-Dutch law principles on positive prescription were changed and abolished2 by way of introduction of English law in 1871.3 Thus current Sri Lankan law on positive prescription is a mixture of both Roman-Dutch and English law principles. Prescription Ordinance 1871 contains specific provisions to regulate law relating to acquiring land ownership by adverse possession. By fulfilling these requirements4 an adverse possessor can acquire ownership to a plot of land. The registration of documents system was introduced to Sri Lanka in 1863.5 There were previous attempts to introduce Title Registration to Sri Lanka;6 registration of documents system prevailed till 1998 as none of these attempts were successful. Title Registration Act which is operational now was enacted in 1998. The Act is currently being implemented in various parts of the country7 and is expected to be fully implemented by the year 2020, and till then, both systems will function as parallels. Registration of prescriptive title to a land based on adverse possession is accepted under registration of documents system and, Prescription Ordinance and Registration of Documents Ordinance were functional together without any conflict. Nevertheless, law of positive prescription was abolished by section 57 of Registration of title Act in 1998. Consequently prescription will not be considered as a method of acquiring ownership to lands in Sri Lanka after Torrance system is fully implemented. This paper intends to research whether this is essential and justifiable in a Torrance system and also whether Sri Lanka should abolish prescriptive ownership to land entirely. The paper would also bring suggestions to amend section 57 of registration of title act of 1998.